An integrated multi-objective optimization approach to determine the optimal feature processing sequence and cutting parameters for carbon emissions savings of CNC machining. Issue 6 (2nd June 2020) - Tian, Changle; Zhou, Guanghui; Lu, Fengyi; Chen, Zhenghao; Zou, Liang
ABSTRACT: Carbon emissions caused by CNC machining attract increasing attentions. It has been proved that carbon emissions and processing time are jointly affected by process routes and cutting parameters. Cutting parameters and process routes optimization, however, are traditionally carried out separately and sequentially, limiting the potential of carbon emissions reduction. To further reduce carbon emissions, an integrated approach of features processing sequence and cutting parameters optimization is proposed to minimize the carbon emissions and processing time. Firstly, a multi-objective optimization model for minimizing carbon emissions and processing time is proposed. Secondly, an NAGS-II algorithm is designed to solve the proposed model. Then, case studies are conducted to verify the feasibility and validity of the proposed integrated optimization approach. Case studies and comparative analysis with other literature show that: i) integrated optimization of features processing sequence and cutting parameters can achieve more carbon emissions savings than features processing sequence optimization with preset cutting parameters; ii) the proposed multi-objective integrated optimization method can strike a trade-off between carbon emissions and processing time.